Filogenia e classificação do gênero Chinavia orian (Hemipterra: pentatomidae) com ênfase na evolução da genitália no grupo geniculata - Genevcius, Bruno Celso [UNIFESP] (2014)
The geniculata group comprises 13 species widely distributed in the South America. As well as for nearly all lineages of Heteroptera, the genitalia in the group are poorly understood, and the underlying evolutionary mechanisms are far from understood. Male genitalia are often used in taxonomic and phylogenetic studies of animals, since they have high evolutionary rates and high interspecific variability. On the other hand, female genitalia are frequently neglected, being very often a priori considered as non-informative and invariable among closely related taxa. However, evidence is increasing over the last years in favor of species-specific female genitalia as a result of intersexual coevolution. The goals of this work were: to test the monophyly of the geniculata group, to conduct a taxonomic revision, to assess the degree of genital specificity in males and females of the group and to test whether there is a pattern of correlated evolution between male and female genitalia from a macroevolutionary perspective. The geniculata group was recovered as monophyletic, and the male and female genitalia showed a clear pattern of correlated evolution. The evolutionary mechanisms associated to these patterns are discussed.